Implication of the Identification of an Earlier Pseudorabies Virus (PRV) Strain HLJ-2013 to the Evolution of Chinese PRVs - Liu, Huimin; Shi, Zhibin; Liu, Chunguo; Wang, Pengfei; Wang, Ming; Wang, Shida; Liu, Zaisi; Wei, Lili; Sun, Zhenzhao; He, Xijun; Wang, Jingfei (Frontiers in Microbiology, 2020)
Pseudorabies viruses (PRVs) pose a great threat to the pig industry of many countries around the world. Human infections with PRV have also been reported occasionally in China. Therefore, understanding of the epidemiology and evolution of PRVs is of great importance for the disease control in the pig populations and humans as well. In this study, we isolated a pseudorabies virus designated HLJ-2013 from PRV-positive samples that had been collected in Heilongjiang, China, in 2013. The full genome sequence of the virus was determined to ~143 kilobase pairs (kbp) in length using high-throughput sequencing. The genomic sequence identities between this isolate and 21 other previous PRV isolates ranged from 92.4% (with Bartha) to 97.3% (with SC). Phylogenetic analysis based on the full-length genome sequences revealed that PRV HLJ-2013 clustered together with all the Chinese strains in one group belonging to Genotype II, but this virus occurred phylogenetically earlier than all the other Chinese PRV strains. Phylogenetic trees based on both protein-coding genes and non-coding regions revealed that HLJ-2013 probably obtained its genome sequences from three origins: a yet unknown parent virus, the European viruses, and the same ancestor of all Chinese PRVs. Recombination analysis showed that HLJ-2013-like virus donated possibly the main framework of the genome of the Chinese PRVs. HLJ-2013 exhibited cytopathic and growth characteristics similar to that of the Chinese PRV strains SC and HeN1, but its pathogenicity in mice was higher than that of SC and lower that of HeN1. The identification of HLJ-2013 takes us one step closer to understanding the origin of PRVs in China and provides with new knowledge about the evolution of PRVs worldwide.